Building Muslim Youth with Noble Character and Morals Through the PETANU (Pembekalan Tunas Aswaja) Program at MTs Unggulan Nurul Qur'an Boyolali - Khassan Masyath; Muhammad Saiful Hidayat; Siti Asdiqoh (World Journal of Islamic Learning and Teaching, 2024)
The PETANU (Pembekalan Tunas Aswaja) activity aims to equip young Muslim generations with relevant knowledge and skills, enabling them to grow into individuals with strong character and noble morals. This activity was conducted due to the lack of comprehensive understanding among the younger generation regarding Aswaja teachings, as well as the limited opportunities for them to practice these values in their daily lives. The methods employed in this activity include training sessions, group discussions, and practical applications. This research adopts a qualitative descriptive approach. The study is based on existing books, journals, and articles. The researcher merely collected and analyzed data from these sources without conducting additional experiments. The objective is to delve deeper into the research topic. The training materials covered the history of Aswaja, creed, worship, ethics, and the role of youth in da'wah. The results of this community service activity include an increased understanding of Aswaja values among participants, a growing awareness of the importance of noble character, and the formation of a social network among participants. Additionally, participants demonstrated a high level of enthusiasm for applying the knowledge gained in their daily lives and surrounding environment.